2018
DOI: 10.3389/fimmu.2018.01995
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Expression on Mycobacterium tuberculosis-Specific CD4 T Cells Is Associated With Bacterial Load in Human Tuberculosis

Abstract: Persistent antigen stimulation in chronic infections has been associated with antigen-specific T cell dysfunction and upregulation of inhibitory receptors, including programmed cell death protein 1 (PD-1). Pulmonary tuberculosis (TB) disease is characterized by high levels of Mycobacterium tuberculosis (Mtb), yet the relationship between bacterial load, PD-1 expression, and Mtb-specific T cell function in human TB has not been well-defined. Using peripheral blood samples from adults with LTBI and with pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 79 publications
3
54
0
Order By: Relevance
“…Expression of PD‐1 on T cells, MAIT cells and NK cells from patients with TB was elevated, and blockage of PD‐1 and/or its ligands improves functions of T cells, MAIT cells and NK cells . PD‐1 expression on Mtb ‐specific CD4 T cells correlates with bacterial load and decreases after successful anti‐TB drug treatment . Bronchoalveolar lavage from patients with military TB had significantly higher PD‐1 + T cells with diminished production of IFN‐γ and TNF‐α .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of PD‐1 on T cells, MAIT cells and NK cells from patients with TB was elevated, and blockage of PD‐1 and/or its ligands improves functions of T cells, MAIT cells and NK cells . PD‐1 expression on Mtb ‐specific CD4 T cells correlates with bacterial load and decreases after successful anti‐TB drug treatment . Bronchoalveolar lavage from patients with military TB had significantly higher PD‐1 + T cells with diminished production of IFN‐γ and TNF‐α .…”
Section: Discussionmentioning
confidence: 99%
“…15,16,[21][22][23] PD-1 expression on Mtb-specific CD4 T cells correlates with bacterial load and decreases after successful anti-TB drug treatment. 24,25 Bronchoalveolar lavage from patients with military TB had significantly higher PD-1 + T cells with diminished production of IFN-γ and TNF-α. 26 Although PD-1 −/− mice had highly enhanced Th1 responses during Mtb infection, they showed severe and lethal immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Without doubt, these data raise questions regarding the role of PD‐1 on T cells. One possible explanation for the observation is that signal transduction via the PD‐1 pathway during chronic viral infections are inherently different from those that occur during chronic bacterial infections . PD‐1 is not a marker of exhaustion in T cells in TB is that previous studies focused on viral‐specific CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the observation is that signal transduction via the PD-1 pathway during chronic viral infections are inherently different from those that occur during chronic bacterial infections. 22,36,37 PD-1 is not a marker of exhaustion in T cells in TB is that previous studies focused on viralspecific CD8 T cells. Lineage-specific differences may result from the utilization of different signaling pathways in the T-cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…HIV increases the likelihood of anergy 34 , but in some cohorts up to 46% of HIV-negative TB cases are anergic 40 . Modern immune analysis has characterized TB-induced immune exhaustion demonstrating that TB patients have decreased IFN-γ, IL-2 and proliferative capacity with an increase in immune checkpoint inhibitors, such as PD-1, TIM3 and CTLA-4 18,19,41,42 . In addition to limiting critical cytokines, such as IFN-γ, previous studies have demonstrated that immune cells from TB patients to have downstream defects in cell signaling including decreased IFN-γ-inducible gene expression 43,44 .…”
Section: Discussionmentioning
confidence: 99%